Strategy for supporting community health agents in mental health actions in Salvador-BA - Silva, Cristiane Batista da; Santos, Josenaide Engrácia dos; Souza, Rozemere Cardoso de (Saúde e Sociedade, 2012)
This paper describes an intervention offering matrix support, a model for integrating mental health care in Family Health Strategy (FHS). In this model, technical-pedagogical and specialized services are offered to the primary care team, helping them to provide care to the patients in the dynamics of their own territory. OBJECTIVE: To report the experience of offering matrix support to Community Health Agents in the district of Saramandaia (Salvador, Bahia), which tried to formulate new possible relations between mental health and family health. METHODS: The experience was the result of a survey entitled "Social construction of learning in mental health and family health" and from the contacts with the team. Researchers made a point of respecting three essential aspects of qualitative research: approval by the Ethics in Research Committee, anonymity and protection against the abuse of power in the relationship between researcher and participants. Matricial support was offered through in-service training meetings, cases meetings and home visits. RESULTS: Matrix support contributed to a collective construction of knowledge in mental health care, and created a "care space" for Community Health Agents. Besides, it fostered the construction of support networks linking social actors involved, since the articulation between mental health and family health, citizenship and personal autonomy over one's own health are considered important.